Functional Analysis of Zebrafish Paralogs, parla and parlb, by CRISPR-Cas9 Mediated Mutagenesis - Jung, Megan (Université d'Ottawa / University of Ottawa, 2017)
Parkinson’s disease is a highly prevalent multifactorial neurodegenerative disorder caused by a complex cascade of interactions between various genetic and environmental factors. Due to this, the majority of cases are termed idiopathic. However, about 10% of PD cases are due to defined genetic factors. Interestingly, both idiopathic and familial cases of PD share mitochondrial dysfunction as a central component in the pathology of the disease. The mitochondrial protease, presenilin-associated rhomboid-like (PARL), is one such Parkinson's disease-linked gene, and is associated with diverse processes including mitochondrial dynamics, active inhibition of unnecessary apoptosis and mitophagy in Drosophila and yeast. Here, I investigated the role of the two zebrafish parl paralogs, parla and parlb, through stable CRISPR-Cas9 mediated mutagenesis. I injected wild type embryos with sgRNAs targeting parla and parlb loci, successfully producing indel mutations in parlb and multi-exon deletions in parla at mutation efficiencies of 74% and 40%, respectively. Through whole mount in situ hybridization experiments against th1, I saw no change in dopaminergic (DA) neuron development displayed by parlb mutants compared to wild types. Injection of parla splice blocking morpholinos into parlb mutants indicates that proper DA neuron development may depend principally on Parla function and loss of both Parla and Parlb function increases larval mortality. These results suggest a negative epistatic relationship between the parl paralogs as seen by the more severe phenotype observed in the loss of both Parla and Parlb function compared to the individual effects.
Keywords: PARL; Paralogs; Zebrafish; CRISPR-Cas9; Parkinson's Disease